1998
DOI: 10.1021/bi971356z
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Binding Studies of Photosystem II Using a Calcium-Selective Electrode

Abstract: The identification of Ca2+ as a cofactor in photosynthetic O2 evolution has encouraged research into the role of Ca2+ in photosystem II (PSII). Previous methods used to identify the number of binding sites and their affinities were not able to measure Ca2+ binding at thermodynamic equilibrium. We introduce the use of a Ca2(+)-selective electrode to study equilibrium binding of Ca2+ to PSII. The number and affinities of binding sites were determined via Scatchard analysis on a series of PSII membrane preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 46 publications
(74 reference statements)
1
37
0
Order By: Relevance
“…Calcium was included in the fit combination because it has been implicated as a structural element of the OEC through O 2 evolution activity (19,45,(62)(63)(64)(65)(66), EPR (20), and calcium-and strontium-EXAFS experiments (22,23). In conventional EXAFS experiments it was noticed previously that the addition of the manganese-calcium vector to the manganese-manganese long interaction improves fit qualities.…”
Section: Ft Peak Iii; Orientation Of the Long Manganese-manganese Andmentioning
confidence: 99%
“…Calcium was included in the fit combination because it has been implicated as a structural element of the OEC through O 2 evolution activity (19,45,(62)(63)(64)(65)(66), EPR (20), and calcium-and strontium-EXAFS experiments (22,23). In conventional EXAFS experiments it was noticed previously that the addition of the manganese-calcium vector to the manganese-manganese long interaction improves fit qualities.…”
Section: Ft Peak Iii; Orientation Of the Long Manganese-manganese Andmentioning
confidence: 99%
“…When photosynthetic electron transport is allowed to proceed, Ca 2ϩ that is taken up during the day does not accumulate in the stroma as free Ca 2ϩ ; rather, it is either transported into other compartments (e.g., the thylakoid) or bound (Kreimer et al, 1987). It has been reported that Ca 2ϩ performs vital functions in the thylakoid (Becker et al, 1985;Miller and Brudvig, 1989;Grove and Brudvig, 1998). A Ca 2ϩ /H ϩ antiporter has been characterized from thylakoids (Ettinger et al, 1999), and it is attractive to consider the possibility that this antiporter transports Ca 2ϩ into the thylakoid, driven by the proton electrochemical gradient generated by photosynthetic electron transport.…”
Section: A Dark-dischargeable Ca 2ϩ Storementioning
confidence: 99%
“…On the other hand, within the thylakoid, functional assembly of photosystem II (PSII) and the oxygen-evolving complex requires proper assembly of polypeptides and cofactors in a process that is light and Ca 2 ϩ dependent (Becker et al, 1985;Miller and Brudvig, 1989;Grove and Brudvig, 1998). This Ca 2 ϩ dependence is relevant not only to the initial assembly of the PSII/oxygen-evolving complex and to the repair of PSII reaction centers that have been damaged by photoinhibition during a normal day (Mattoo et al, 1989) but also to the mechanism of photosynthetic oxygen evolution (Yocum, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…A second Ca 2+ atom was found to be tightly bound to antenna proteins (Han and Katoh 1993), probably CP29 (Jegerschö ld et al 2000). Binding of Ca 2+ has also been examined under static (dark) conditions with an ion-specific electrode (Grove and Brudvig 1998 (Vrettos et al 2001a;van Gorkom and Yocum 2005) with regard to the ability of inhibitory metals to occupy the Ca 2+ site. The lanthanides that have been tested are all effective at low (50-100 lM) concentrations, and tend to produce inhibitions that are difficult to reverse (Ghanotakis et al 1985;Bakou et al 1992).…”
Section: Introductionmentioning
confidence: 99%